Increasing Job Satisfaction, Organizational Commitment and the Requirement for Competence and Training - Setyo Riyanto; Unang Toto Handiman; Mikaria Gultom; Adriani Gunawan; Juniawan M. Putra; Hendro Budiyanto (Ital Publication, 2023)
Many studies have examined the relationship between training and employee job satisfaction, the relationship between employee training and organizational commitment, the relationship between competence and employee job satisfaction, and the relationship between competence and organizational commitment, but there are still many unanswered questions. In particular, research has not explained how training and competence directly affect job satisfaction and managerial competence and how training and competence indirectly affect organizational commitment through job satisfaction. Therefore, this study investigates how training and competence directly affect job satisfaction and organizational commitment. Indirectly, training and competence affect organizational commitment through job satisfaction. Survey-based data collection was collected by purposive sampling, which included 280 employees from BPJS who participated in the training. The findings from the path analysis, along with measurements and structural tests, are very supportive of the employee training program. The findings show that employee training and competence directly affect job satisfaction and organizational commitment. The findings also show that training and employee competence indirectly affect organizational commitment through job satisfaction. Finally, employee job satisfaction affects managerial competence. This study shows that employee training is an effective way for organizations to achieve their goals. Doi: 10.28991/ESJ-2023-07-02-016 Full Text: PDF